Increases in tumor N-glycan polylactosamines associated with advanced HER2-positive and triple-negative breast cancer tissues - Scott, Danielle A.; Kriegsmann, Mark (Proteomics. Clinical applications, 2019)
Purpose Using a recently developed matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) method, human breast cancer formalin-fixed paraffin-embedded (FFPE) tissue sections and tissue microarrays (TMA) are evaluated for N-linked glycan distribution in the tumor microenvironment. Experimental design Tissue sections representing multiple human epidermal growth factor receptor 2 (HER2) receptor-positive and triple-negative breast cancers (TNBC) in both TMA and FFPE slide format are processed for high resolution N-glycan MALDI-IMS. An additional FFPE tissue cohort of primary and metastatic breast tumors from the same donors are also evaluated. Results The cumulative N-glycan MALDI-IMS analysis of breast cancer FFPE tissues and TMAs indicate the distribution of specific glycan structural classes to stromal, necrotic, and tumor regions. A series of high-mannose, branched and fucosylated glycans are detected predominantly within tumor regions. Additionally, a series of polylactosamine glycans are detected in advanced HER2+, TNBC, and metastatic breast cancer tissues. Comparison of tumor N-glycan species detected in paired primary and metastatic tissues indicate minimal changes between the two conditions. Conclusions and clinical relevance The prevalence of tumor-associated polylactosamine glycans in primary and metastatic breast cancer tissues indicates new mechanistic insights into the development and progression of breast cancers. The presence of these glycans could be targeted for therapeutic strategies and further evaluation as potential prognostic biomarkers.
First published: 28 December 2018
Gesehen am 24.10.2019